Characteristics of moringa leaf powder as fortification and consumer acceptance. Issue 1 (1st May 2022) - Handayani, Y; Aminah, S; Yanis, M; Waryat
Abstract: Moringa Oleifera is not only rich in nutrients but also has functional properties with efficacies and benefits for human health. Moringa leaf powder as an intermediate product can be used as a fortification to enrich nutrition in food products in an acceptable concentrate for consumers. This study aims to determine the physical and chemical characteristics of Moringa leaf powder and the level of consumer acceptance of the fortification product. The research included the process of making Moringa leaf powder until the preeminent temperature and drying time were obtained and the use of Moringa leaf powder as a fortification in ice cream. Fortification of ice cream used four treatments of the powder concentration in 0.5%, 1%, 1.5% and 2%. The results showed the yield of the powder was 25%, with a 7.80 % water content at a temperature of 47° – 50 °C for five hours. The level of consumer acceptance of fortified ice cream shows the same acceptance of color, aroma, texture, except taste. Consumers prefer formulas with a concentration of 1% Moringa powder, 5% creamer, 15% sugar, 0.5 % CMC, and 78.5 % milk. Moringa aroma and taste have an impact on consumer acceptance of Moringa ice cream.